Gender Preference, Attitude and Awareness Regarding Sex Determination Among Married Women Attending General OPD & Antenatal Clinic of RDGMC Ujjain, MP, India - Khandelwal, Vidit; Chakole , Swarupa V; Gupta , Harshal; Mehta , Satish C (National Journal of Community Medicine, 2012)
Background: The preference for a son and female feticide continues to be a prevalent norm in traditional Indian household resulting in declining sex ratio, which has dropped to alarming level. Objective: To evaluate gender preference, attitude and awareness regarding sex determination among married women attending general OPD, antenatal clinic of RDGMC UJJAIN, MP, INDIA. Material and methods: Study was conducted in February - March 2011 that enroll 400 married women of reproductive age group attending general OPD, antenatal clinic of RDGMC Ujjain, MP, India. A predesigned questionnaire was used to elicit information on socio-demographic and SES of study subjects and assessing their knowledge, attitude and practice regarding sex determination as: preference, reason for preference. Result: Preferred gender composition was equal no of boy & girls ( 64.5 %) & more boys than girls(23%). 79 % of women were aware about place for sex determination. 69.5 % of women were aware to fact that fetal sex Determination is a crime & 66.5 % of women knew about the punishment for sex determination and implication of feticide. male child preference observed in 40 % of women. Conclusion: Despite the existence of preconception and prenatal diagnostic technique (PNPCDT), there is dire need to strengthen their law.